2014
DOI: 10.1089/neu.2014.3405
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Inflammatory Cytokines and Chemokines in Naturally Occurring Canine Spinal Cord Injury

Abstract: Canine intervertebral disk herniation (IVDH) is a common, naturally occurring form of spinal cord injury (SCI) that is increasingly being used in pre-clinical evaluation of therapies. Although IVDH bears critical similarities to human SCI with respect to lesion morphology, imaging features, and post-SCI treatment, limited data are available concerning secondary injury mechanisms. Here, we characterized cerebrospinal fluid (CSF) cytokines, and chemokines in dogs with acute, surgically treated, thoracolumbar IVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Apart from these studies, Kwon et al [ 5 ] indicated a positive correlation between IL-6 and IL-8 CSF levels and the severity of neurological impairment. These results were affirmed in further animal studies [ 10 , 21 ]. Unfortunately, they did not have a follow-up and, therefore, could not study the regenerative aspect of different factors.…”
Section: Discussionsupporting
confidence: 67%
“…Apart from these studies, Kwon et al [ 5 ] indicated a positive correlation between IL-6 and IL-8 CSF levels and the severity of neurological impairment. These results were affirmed in further animal studies [ 10 , 21 ]. Unfortunately, they did not have a follow-up and, therefore, could not study the regenerative aspect of different factors.…”
Section: Discussionsupporting
confidence: 67%
“…[20][21][22] However, neither of those methods alone provides prognostic accuracy superior to that of testing for deep pain perception. Measurement of various biomarker concentrations in serum or CSF [23][24][25][26] holds considerable promise for future prognostication but is insufficiently sensitive and specific at present.…”
Section: Confidence Interval Ivdhmentioning
confidence: 99%
“…By contrast, dogs with complete injuries (paraplegic with no pain sensation in either hind limb or tail) have a 50%‐60% chance of recovery that cannot be reliably predicted from the neurological examination . Many groups have evaluated different prognostic biomarkers in this group of dogs including quantification of magnetic resonance imaging (MRI) findings, and measurement of inflammatory mediators and neural proteins found in cerebrospinal fluid (CSF) . Although useful, these approaches involve considerable cost (MRI) and are clinically invasive (CSF sampling).…”
Section: Introductionmentioning
confidence: 99%